The importance of human capital with the focus on generation Y - Pouchová, Lenka (Univerzita Pardubice, 2011)
The article praises the importance of human capital for competitiveness and prosperity of a company. To achieve business goals and long term sustainability companies seek to attract and keep young talents and nurture tomorrow’s leaders. Selected survey shows that young generation of workers has different expectations and needs in the world of work which should to be considered by human resources management. Finally, this paper examines the human resources policy of the company Robert Bosch, Ltd. in České Budějovice and its approach to the young generation.
Keywords: human capital; generation Y; human resources management; workforce